Platinum anticancer drugs and photochemotherapeutic agents: recent advances and future developments. (1st March 2014) - Shaili, Evyenia
Platinum-based chemotherapeutic drugs such as cisplatin, carboplatin and oxaliplatin are widely applied for the treatment of various types of tumours. Over the last few decades, a large variety of Pt(II) and Pt(IV) complexes have been developed to improve the applicability in a wider spectrum of cancers, increase their therapeutic window and reduce the dose-limiting side effects. Photodynamic therapy (PDT), which is the administration of a photosensitiser followed by visible light activation, is a promising route to avoid damage to healthy cells and the surrounding tissue. Transition metal complexes as photochemotherapeutic agents are an attractive option for further development in the field of photoactivated chemotherapy (PACT). These complexes exhibit different numbers and types of excited states which are easily accessible upon light irradiation, subsequently giving rise to the formation of various photoproducts that can enable a distinct mode of action. Platinum – diazido complexes are promising candidates for PACT due to the low cytotoxicity when irradiated with visible light. This review summarises the mode of action of current platinum anticancer drugs with cisplatin as a lead example and the development of non-conventional Pt(II) complexes. Background information regarding PDT, the photophysical and photochemical properties of metal complexes is provided, as well as notable examples of photoactivated metal complexes with biological activity. Particular emphasis is placed on recent developments on platinum photoactivated drugs.